Production of Branding Model for Health Services Based on Clients' Expectations Approach - Masoomeh Abdi Talarposhti; Ghahraman Mahmoudi Alemi; Mohammad Ali Jahani (Tehran University of Medical Sciences, 2021)
Background and Aim: One of the reasons that caused healths clients are feeling dissatisfaction with health organizations is expectations that they are creating and not able to meet according to their expectations. Therefore, the present study was conducted with the aim of production a branding model for health services with the of clients' expectations approach. Materials and Methods: This compound study was performed in 2021. The statistical population of this study in qualitative phase included 20 academic and institutional experts using snowball sampling and the Delphi technique. For the quantitative phase, 830 people referred to health centers were selected as service recipients. The validity of the questionnaire was confirmed by face, content, and structural validity, and its reliability was confirmed by Cronbach's alpha of 0.96 Quantitative data were presented by EQS software version 6.1 with confirmatory factor analysis and using structural equations. Results: The results of factor structure in healthcare branding based on six main themes of competitive position, brand equity, brand accessibility, brand consolidation in the minds of clients and the market, branding strategies, and consumer-brand relationship with 19 sub-themes based on the perspective of health services clients (CFI=0/9, TLI=0/9, SRMR=0/049, RMSEA=0/09) had a good fit and the internal consistency of the items had significant levels (P<0/05). Conclusion: The results of this study show that 19 sub-main themes confirm the six-factor structure of health services branding and were one of the effective themes in branding from the perspective of clients. Since the branding of health services improves the quantity and quality of services provided in the health system, therefore, it is suggested that by creating innovation in the quantity and quality of services provided, access to health services, creating a competitive advantage and empowering employees and improving communication skills, an effective step can be taken in health services branding planning.